Odpowiedź :
[tex]a_n=a_1+(n-1)*r[/tex]
Zad. 1
[tex]a_{46}=-96\\r=2\\a_{46}=a_1+(46-1)*2\\-96=a_1+45*2\\-96=a_1+90 /-90\\-96-90=a_1\\a_1=-186[/tex]
Zad.2
[tex]a_n=3n-1\\83=3n-1/+1\\84=3n/:3\\28=n[/tex]
Odp. Liczba 83 jest 28 wyrazem tego ciagu.
Zad. 3
[tex]a_1=35\\a_2=?\\a_3 =?\\a_4=?\\a_5=-15\\-15=35+4r /-35\\-50=4r/:4\\r=-12.5\\a_2=22.5\\a_3=10\\a_4=-2.5\\[/tex]
Zad. 4
[tex]a_1=4x-1\\a_2=x+6\\a_3=5x-2\\a_2=a1+r\\a_2-a_1=r\\\\x+6-(4x-1)=r\\r=x+6-4x+1\\r=-3x+7\\\\a_3=a_1+2x\\5x-2=4x-1+2(-3x+7)\\5x-2=4x-1-6x+14\\5x-4x+6x=-1+14+2\\7x=15:7\\x=\frac{15}7=2\frac17\\\\a_1=4(2\frac17-1)=4*1\frac17=4*\frac87=\frac{32}7=4\frac47\\a_2=2\frac17+6=8\frac17\\a_3=5(2\frac17-2)=5*\frac17=\frac57[/tex]
Zad. 5
[tex]a_1=3\\r=-5\\S_n=\frac{a_1+a_n}{2}*n\\a_n=a_1+(n-1)*r\\a_{43}=3+(43-1)*(-5)\\a_{43}=3+42*(-5)\\a_{43}=3+(-210)\\a_{43}=3-210\\a_{43}=-207\\S_{43}=\frac{3-207}{2}*43\\S_{43}=\frac{-204}{2}*43\\S_{43}=-102*43\\S_{43}=-4386[/tex]
Odpowiedź:
1)
an = a¹ + (n-1)×r
-96 = a¹ + (-96-1)×2
-96 = a¹ - 194
a¹ = 194 - 96
a¹ = 98
2)
an = 3n - 1 = 83
3n = 84
n = 28
odp. jest 28 wyrazem
3)
35, a², a³, a⁴, -15
a¹ = 35
a⁵ = -15
an = a¹ + (n-1)×r
-15 = 35 + 4r
-50 = 4r
r = -12,5
a² = 35 + (-12,5) = 22,5
a³ = 35 + 2×(-12,5) = 35 - 25 = 10
a⁴ = 35 + 3×(-12,5) = 35 - 37,5 = -2,5
4)
4x-1, x+6, 5x-2
(5x-2) - (x+6) = (x+6) - (4x-1) = r
4x - 8 = -3x + 7
7x = 15
x = 15/7
4×15/7 - 1 = 60/7 - 7/7 = 53/7 = 7 4/7
x+6 = 2 1/7 + 6 = 8 1/7
5×15/7 - 2 = 75/7 - 14/7 = 61/7 = 8 5/7
7 4/7, 8 1/7, 8 5/7
5)
a¹ = 3
r = -5
Sn = (a¹ + an)×n ÷ 2
S⁴³ = (3 + a⁴³)×43 ÷ 2
a⁴³ = a¹ + 42×r
a⁴³ = 3 + 42×(-5)
a⁴³ = 3 - 210
a⁴³ = -207
S⁴³ = (3 - 207)×43 ÷ 2
S⁴³ = (-204)×43 ÷ 2
S⁴³ = (-102)×43
S⁴³ = -4386